A cross-sectional study to assess hearing impairment in school going children aged 6 to10 years of Ranchi City - Kumar, Ambrish (International Journal of Medical Research and Review, 2016)
Introduction: Hearing loss of any type or degree if occurs in infancy or childhood can interfere with the development of a childrens spoken language, academic performance, reading and writing skills. The objective of the present study was to determine the prevalence of hearing impairment among school going children aged 6 to10 years of RANCHI city and to identify the etiological factors of diminished hearing and their distribution patterns. Methods: 810 school going children of 6 to 10 years age group selected from four schools of the city. The schools were selected from 208 schools by simple randomization method encompassing children from all socioeconomic backgrounds. Clinical ENT examination was done followed by otoscopy with a portable otoscope and tuning fork tests with 512 Hz tuning fork, both of which were used as screening tests. Pure Tone Audiometry, which is the confirmatory test for hearing impairment and Tympanometry was done only in suspected cases of Otitis media with effusion (OME). Results: A total of 810 children were examined of which 75 had hearing impairment out of which prevalence rate of hearing impairment was significantly more in girls as compared to boys. There was a statistically significant inverse relationship observed between prevalence of hearing impairment and socioeconomic status. Conclusion: Screening tests at school entry levels and ear health care education in community can minimize prevalence of ear pathologies and hence hearing impairment as most of the causes are treatable.